MISKONSEPSI MATERI FOTOSINTESIS DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) DI SD/MI - Izza Aliyatul Muna (Cendekia: Kependidikan dan Kemasyarakatan, 2012)
Abstract: The quality of science education that is still unsatisfying can be effected by misconceptions and learning conditions that less pay attention to learners’ preconceptions. Misconception is frequently happened among students in all levels of education, including elementary school students, secondary schools students, up to university or college students and even someone who have already worked. The most common misconceptions are caused by the initial concept (preconception) in which it was taken to formal education. As a result, many of elementary school students are encountered with misconception. Since childhood, people have already constructed such concepts through daily experiences, and it is possible to say that they have undergone a process of learning early. The cause of misconceptions that happen to learners are vary, including learners from itself, educators, textbooks, contexts, and methods of teaching. All science materials are possible to create misconception among learners, for instance, photosynthesis. The example of misconceptions in this material include the process of photosynthesis in which students assume that it occurs only during the day with the help of sunlight, only plants whose green leaf that capable to have photosynthesis; chlorophyll present in the leaves alone, as well as plants perform photosynthesis during the day while at night plants do breathe. The misconception is a major problem in learning science as it can disrupt the formation of a scientific conception.